COVID-19 impairs oxygen delivery by altering red blood cell hematological, hemorheological, and oxygen transport properties - Rogers, Stephen C.; Brummet, Mary; Safari, Zohreh; Wang, Qihong; Rowden, Tobi; Boyer, Tori; Doctor, Allan (Frontiers in Physiology, 2024)
Introduction: Coronavirus disease 2019 (COVID-19) is characterized by impaired oxygen (O2) homeostasis, including O2 sensing, uptake, transport/delivery, and consumption. Red blood cells (RBCs) are central to maintaining O2 homeostasis and undergo direct exposure to coronavirus in vivo. We thus hypothesized that COVID-19 alters RBC properties relevant to O2 homeostasis, including the hematological profile, Hb O2 transport characteristics, rheology, and the hypoxic vasodilatory (HVD) reflex. Methods: RBCs from 18 hospitalized COVID-19 subjects and 20 healthy controls were analyzed as follows: (i) clinical hematological parameters (complete blood count; hematology analyzer); (ii) O2 dissociation curves (p50, Hill number, and Bohr plot; Hemox-Analyzer); (iii) rheological properties (osmotic fragility, deformability, and aggregation; laser-assisted optical rotational cell analyzer (LORRCA) ektacytometry); and (iv) vasoactivity (the RBC HVD; vascular ring bioassay). Results: Compared to age- and gender-matched healthy controls, COVID-19 subjects demonstrated 1) significant hematological differences (increased WBC count—with a higher percentage of neutrophils); RBC distribution width (RDW); and reduced hematocrit (HCT), Hb concentration, mean corpuscular volume (MCV), and mean corpuscular hemoglobin concentration (MCHC); 2) impaired O2-carrying capacity and O2 capacitance (resulting from anemia) without difference in p50 or Hb–O2 cooperativity; 3) compromised regulation of RBC volume (altered osmotic fragility); 4) reduced RBC deformability; 5) accelerated RBC aggregation kinetics; and (6) no change in the RBC HVD reflex. Discussion: When considered collectively, homeostatic compensation for these RBC impairments requires that the cardiac output in the COVID cohort would need to increase by ∼135% to maintain O2 delivery similar to that in the control cohort. Additionally, the COVID-19 disease RBC properties were found to be exaggerated in blood-type O hospitalized COVID-19 subjects compared to blood-type A. These data indicate that altered RBC features in hospitalized COVID-19 subjects burden the cardiovascular system to maintain O2 delivery homeostasis, which appears exaggerated by blood type (more pronounced with blood-type O) and likely plays a role in disease pathogenesis.